2023
DOI: 10.1002/advs.202205566
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Dissection of the Transportation and miRNA‐Release Dynamics of Small Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are cell‐derived membrane‐enclosed structures that deliver biomolecules for intercellular communication. Developing visualization methods to elucidate the spatiotemporal dynamics of EVs’ behaviors will facilitate their understanding and translation. With a quantum dot (QD) labeling strategy, a single particle tracking (SPT) platform is proposed here for dissecting the dynamic behaviors of EVs. The interplays between tumor cell‐derived small EVs (T‐sEVs) and endothelial cells (ECs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Recent studies have shown that content miRNA plays an important role in the function of EV. 63 , 64 In the animal model of myocardial infarction, EV exerts anti‐apoptotic effects and promotes cardiac tissue and functional recovery by delivering miR‐21 to endothelial cells and cardiomyocytes. 65 In the rat SCI model, EV loaded with miR‐29 transmits miR‐29 to nerve cell, promoting motor and sensory function repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that content miRNA plays an important role in the function of EV. 63 , 64 In the animal model of myocardial infarction, EV exerts anti‐apoptotic effects and promotes cardiac tissue and functional recovery by delivering miR‐21 to endothelial cells and cardiomyocytes. 65 In the rat SCI model, EV loaded with miR‐29 transmits miR‐29 to nerve cell, promoting motor and sensory function repair.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that following clathrin‐mediated endocytosis by ECs, T‐sEVs are transported to the perinuclear region in a typical three‐stage pattern. Importantly, T‐sEVs frequently interact with and finally enter lysosomes, followed by a quick release of their carried miRNAs 12 . The proliferation, migration, and tube formation of ECs are finely controlled by T‐EVs via multiple pathways.…”
Section: Tumor Cell‐derived Evs In Angiogenesismentioning
confidence: 99%
“…Quantum dots (QDs) are promising fluorescent probes due to their advantages of broad excitation, narrow emission, and stable luminescence and are widely used for fluorescent labeling of biomaterials . QD-based single-particle tracking (QSPT) has emerged as a robust technique for investigating dynamic information on biomolecules and has been extensively used to investigate the dynamic mechanisms of virus infection in live cells. QDs with different emission wavelengths are used to label distinct viral components that help to obtain dynamic information on the infection pathway and genome release of labeled viruses by SPT. However, although our group has previously used QDs to track exosomes by labeling the membrane structure, , a simultaneous dual-color labeling strategy for the internal and external components of exosomes with QDs is still lacking, which is of great importance for the real-time tracking of individual exosomes and elucidating the role of the exosome during virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…19−25 QDs with different emission wavelengths are used to label distinct viral components that help to obtain dynamic information on the infection pathway and genome release of labeled viruses by SPT. 26−33 However, although our group has previously used QDs to track exosomes by labeling the membrane structure, 34,35 a simultaneous dual-color labeling strategy for the internal and external components of exosomes with QDs is still lacking, which is of great importance for the real-time tracking of individual exosomes and elucidating the role of the exosome during virus infection.…”
Section: Introductionmentioning
confidence: 99%